The Impact of Policy Quality and Political Stability on Foreign Direct Investment in ASEAN Countries: An Institutional Economics Analysis - Priyadi, Unggul; Susantun, Indah; Shidiqie, Jannahar Saddam Ash (Journal of Ecohumanism, 2024)
This study investigates the impact of policy quality and political stability on foreign direct investment (FDI) within ASEAN countries. Both components are essential elements of a country’s political risk profile; a lower risk profile characterised by robust policy quality and political stability tends to attract investors. We employ a panel data regression analysis across seven ASEAN countries, Indonesia, Malaysia, Singapore, Thailand, Vietnam, the Philippines, and Brunei Darussalam, from 2012 to 2022 to examine these relationships. The Common Effects Model emerged as the optimal panel model for our analysis. Our results reveal that policy quality negatively impacts foreign direct investment, suggesting that the perceived policy environment in the ASEAN may deter investors. Conversely, political stability exerts a positive effect, indicating that stable political conditions in the ASEAN attract investor interest. These findings affirm that policy quality and political stability are critical factors influencing foreign direct investment within ASEAN countries, underscoring their importance for potential investors. Contribution/Originality: This research offers a fresh perspective to the scholarly discourse on foreign direct investment within the backdrop of policy quality and political stability. The study’s novelty lies in its exploration of these dual factors’ effect on foreign direct investment, specifically within ASEAN countries. Furthering this original contribution, this study also presents a robust application of panel data regression analysis in evaluating regional investment attractiveness.